Raw Material Regulates Flavor Formation via Driving Microbiota in Chinese Liquor Fermentation - Liu, Chongchong; Feng, Shengbao; Wu, Qun; Huang, Heqiang; Chen, Zhanxiu; Li, Shanwen; Xu, Yan (Frontiers in Microbiology, 2019)
Raw material is important for flavors in fermented foods. Here, the effect of hulless barley on the microbiota in Chinese liquor was studied using two main cultivars (heilaoya and dulihuang). Six genera (Lactobacillus, Saccharomyces, Komagataella, Aspergillus, Pichia and Weissella) were identified as flavor producers. Komagataella, mainly correlated with esters, dominated in heilaoya, and Pichia, mainly correlated with carbonyls, dominated in dulihuang. The Mantel test indicated reducing sugar drove the succession of microbiota (heilaoya: P = 0.001; dulihuang: P = 0.006). Especially, glucose (P = 0.0226) and fructose (P = 0.0168) presented the most significant correlations with Pichia and Komagataella, respectively. The simulative fermentation confirmed Komagataella phaffii QK2 grew better in heilaoya with more fructose, whereas Pichia fermentans PF grew better in dulihuang with more glucose. This work highlighted the effect of raw material on microbiota, which would be beneficial for regulating the quality of fermented foods.